Civic Participation in Local Government - Alexander Aleksandrovich Alexandrov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
Article is devoted to a research of level of awareness and practice of participation of the population of the city of Yekaterinburg in local government. Awareness of the population about forms of participation in local government is one of the major factors exerting impact on civil activity of local community. Article purpose - to identify the level of awareness and participation of the population of the city of Yekaterinburg in local government and to develop proposals for their improvement. This article is prepared on the basis of results of the empirical sociological research conducted by authors in May, 2016. In a research the complex of basic sociological methods was used: questionnaire of adult population of the city of Yekaterinburg on the sample representing the city’s population by age and sex (the volume of a sample - 400 people), two focus groups (members of the first focus group were young people aged 18 to 30years, participants in the second - the middleaged 31-40 years), the analysis of officia l documents and information on forms of participation of the population in local government on the official websites of the city of Yekaterinburg. Authors have developed a diagnostic technique which has allowed to reveal the level of awareness of the population of forms of participation of the population of the city of Yekaterinburg in local government. Authors have obtained empirical data on practice of civil participation in local government and have revealed problems which interfere with civil participation in local government. As a result of survey and focus groups the low level of awareness of the population of forms of participation of the population of the city of Yekaterinburg in local government is revealed. The Internet is information source, most convenient for the population, however not enough information on forms of civil participation in local government is posted on the official sites of the city of Yekaterinburg. Authors of article have formulated offers on increase in awareness of the population of Yekaterinburg of forms of participation of the population in local government.